Struktur Puisi Karya John Dami Mukese Serta Relevansinya Dalam Pembelajaran Sastra - Rosa Dalima Bunga; Hawiah Djumadin; Maria Magdalena Rini (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: This study aims to describe the structure of the poem "Autumn" by John Dami Mukese which consists of physical and inner structures and their relevance to the study of literature in high school. This study uses a qualitative approach with qualitative descriptive methods. The data in this study are in the form of words that contain physical and inner structure in the poem "Autumn" by John Dami Mukese. The data source is a collection of books "Jelata Poel Jelata" by John Dami Mukese. Data collection procedures in this study are reading, identifying, modifying, and classifying in accordance with the focus of the study. Data analysis uses in-depth understanding techniques. Checking the validity of the data is done through triangulation techniques. The results of the poem builder research structure consisting of physical structures in the form of: connotative and denotative diction; visual imaging; concrete words; style of personification and repetition; rhyme; and typography. The inner structure of themes; feeling (taste); tone; and mandate. The structure of the builders of "Autumn" poetry by John Dami Mukese can be used as teaching material in the study of literature in high school specifically at KD 3.17 analyzing the elements of poetry builders. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan struktur puisi “Musim Gugur” karya John Dami Mukese yang terdiri atas struktur fisik dan struktur batin dan relevansinya dengan pembelajaran sastra di SMA. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif kualitatif. Data dalam penelitian ini berupa kata-kata yang mengandung struktur fisik dan batin dalam puisi “Musim Gugur” karya John Dami Mukese. Sumber data adalah buku kumpulan “Puisi-Puisi Jelata” karya John Dami Mukese. Prosedur pengumpulan data dalam penelitian ini adalah membaca, mengidentifikasi, mengodifikasi, dan mengklasifikasikan sesuai dengan fokus penelitian. Analisis data menggunakan teknik pemahaman arti secara mendalam. Pengecekan keabsahan  data dilakukan melalui teknik triangulasi. Hasil penelitian struktur pembangun puisi yang terdiri atas struktur fisik berupa: diksi konotatif dan denotatif; pengimajian visual; kata konkret; gaya bahasa personifikasi dan repetisi; rima; dan tipografi. Struktur batin berupa tema; feeling (rasa); nada; dan amanat.  Struktur pembangun puisi “Musim Gugur” karya John Dami Mukese dapat digunakan sebagai bahan ajar dalam pembelajaran sastra di SMA secara khusus pada KD 3.17 menganalisis unsur pembangun puisi.